DevOps for SharePoint With Packer, Terraform, Ansible, and Vagrant - Medina, Oscar (Apress, 2018)
Deploy a SharePoint farm in a repeatable, predictable, and reliable fashion using Infrastructure as Code (IaC) techniques to automate provisioning. Savvy IT pros will learn how to use DevOps practices and open source tools to greatly reduce costs, and streamline management operations for SharePoint farms deployed via Amazon Web Services (AWS), Azure, or on premise. DevOps for SharePoint will help you navigate the complex challenges of deploying and managing SharePoint Server farms. You will learn how to reduce time-consuming tasks and errors when generating development, testing, or production environments. And you will benefit from learning proven methods to apply Microsoft updates with minimal downtime and productivity loss. Whether you are a SharePoint architect, IT pro, or developer helping customers with the SharePoint platform, this book will teach you the most useful DevOps practices to tackle those issues and broaden your skill set. What You'll Learn: Understand the basics of the most popular open source tools-Vagrant, Packer, Terraform, and Ansible-and how to use them in the context of deploying and scaling a SharePoint farm Use Vagrant to build SharePoint development environments in less than an hour, and add automated testing Use Packer to create a "golden image" with preconfigured settings, and then use it as the base image in your Terraform configuration for both AWS and Azure farms Use Terraform to scale your SharePoint farm topology Use Red Hat's Ansible Playbooks to perform configuration management on your farm Use Terraform to deploy immutable infrastructure environments using IaC (Infrastructure as Code) Use InSpec 2.0 to stay in compliance by testing your cloud infrastructure Use Ansible to apply Microsoft updates and patches This book is for IT pros and developers who are looking to expand their knowledge and take a modern approach by using open source technologies to work with Microsoft products. Experience installing SharePoint, and a basic understanding of either Azure or AWS, is helpful. Oscar Medina, CEO and founder of SharePointAce LLC, is a multi-platform senior technologist, consultant, author, and speaker, with more than 16 years of experience. Prior to that, he worked at Microsoft, guiding and supporting Fortune 1000 companies on SharePoint. Oscar is passionate about Azure, Office 365, and SharePoint, particularly in how they are enabled with emerging and open source technologies. Ethan Schumann is a Solutions Architect for Onica, a leading AWS Cloud Consulting Partner. He specializes in automation and DevOps transformations with a focus on enterprise implementations using cloud native services and modern tooling. He has experience designing and implementing various technologies such as Kubernetes containerization, CI/CD constructs for various development workflows, and large-scale Microsoft products, including Sharepoint.